A composite material based on graphite particle core and porous carbon shell, preparation method and application thereof
By using a composite material structure of graphite particle core and porous carbon shell in CVD silicon carbon/graphite anode material, the problem of poor circulation rate performance is solved, and better circulation performance and circulation stability are achieved.
Patent Information
- Application Number
- CN202510012481.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-01
AI Technical Summary
The poor circulation rate performance of CVD silicon carbon/graphite anode material has limited application in high-energy density lithium-ion batteries.
Using a composite material based on the graphite particle core and the porous carbon shell, a graphite particle core-carbon shell structure is formed by carbonizing and activation, and then silicon and coated carbon are vapor deposited to prepare a negative electrode material with improved rate performance and cycle stability.
The rate performance and cycle stability of the negative electrode material are significantly improved. Silicon-carbon materials with slower kinetics are preferred to contact the graphite particles with lithium ions and electrons, making the rate performance of each particle closer.
Smart Images

Figure CN119742355A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries, and relates to a CVD silicon carbon / graphite negative electrode material, specifically a composite material based on a graphite particle core and a porous carbon shell, a preparation method and an application thereof. Background Art
[0002] Negative electrode materials are one of the key materials for lithium-ion batteries, accounting for 10%-15% of the total cost of lithium-ion batteries. Currently, graphite is the mainstream negative electrode material, but it has reached its development limit in terms of energy density. Endurance and energy replenishment anxiety are still one of the key factors that restrict consumers from choosing new energy vehicles. In this context, the development of negative electrode materials that are suitable for high-capacity batteries and fast-charging batteries is an inevitable trend in the development of the lithium-ion battery industry. Silicon-based negative electrode materials with high specific capacity and excellent fast-charging performance have emerged. The theoretical specific capacity of silicon-based negative electrode materials is as high as 4200mAh / g, which is more than ten times that of traditional graphite materials. It can greatly improve the energy density of lithium-ion batteries, thereby increasing the mileage of electric vehicles. It is regarded as the most likely new negative electrode material for large-scale application in the future. However, the expansion / contraction stress generated by silicon-based negative electrode materials during the charging and discharging process causes them to crack severely, resulting in low first efficiency and rapid capacity decay. In addition, silicon-based negative electrode materials are insulators or semiconductors, and their poor electronic conductivity limits their application in high-rate scenarios.
[0003] The most common method to inhibit the expansion of pure silicon negative electrode materials is to use highly stable and highly conductive carbon materials to coat silicon materials or embed silicon materials into carbon materials to prepare silicon-carbon (Si / C) composite materials. The preparation methods of Si / C composite materials include chemical vapor deposition (CVD), mechanical ball milling, spraying, magnesium thermal reduction, sol-gel and pyrolysis. In comparison, the CVD method and mechanical ball milling method with simple process and low cost are more suitable for industrial production and application. However, the Si / C composite materials obtained by mechanical ball milling are prone to agglomeration, resulting in poor battery performance; while the Si / C composite materials prepared by CVD method have high consistency, and the particle agglomeration phenomenon is significantly suppressed. In addition, the Si / C composite materials prepared by this technology also have the advantages of high first coulomb efficiency and high specific capacity. The Si / C composite materials prepared by CVD method can be mainly divided into core-shell structure, yolk-shell structure, porous structure and embedded structure. Among them, the porous structure uses porous carbon as a conductive and buffer substrate, and its nanopore voids (usually less than 5nm) provide sufficient space for the volume expansion of silicon particles. Therefore, the CVD silicon-carbon composite material based on the porous carbon substrate has better cycle stability.
[0004] The preparation of CVD silicon-carbon composite materials on a porous carbon substrate usually involves placing the porous carbon in a high-temperature inert atmosphere, introducing silane, and depositing the nano-silicon particles generated by the cracking of the silane in the porous carbon channels. After further introducing acetylene, a carbon-coated CVD silicon-carbon composite material is obtained. After that, it is necessary to mix the CVD silicon-carbon composite material and graphite in a certain proportion according to the specific capacity requirements to obtain a CVD silicon-carbon / graphite negative electrode material that meets the requirements. In this blending method, since graphite has better ionic and electronic conductivity than CVD silicon-carbon composite materials, at high rates, when graphite has completed the lithium insertion process, the silicon-carbon particles may only be embedded to half the particle depth, and the core of the silicon-carbon particles has not yet reacted. The next lithium ions may be deposited on the surface of the graphite particles to generate metallic lithium. Such differences will affect the rate and cycle performance of the overall battery material. Therefore, it cannot effectively solve the shortcomings of CVD silicon-carbon / graphite negative electrode materials such as poor electronic conductivity, slow lithium ion diffusion, and large volume expansion. The negative electrode materials still face severe challenges in cycle and rate performance, which hinders their expanded application in high energy density lithium-ion batteries. Summary of the invention
[0005] The purpose of the present invention is to provide a composite material based on a graphite particle core and a porous carbon shell, a preparation method and an application thereof, so as to solve the problem of poor cycle rate performance of current CVD silicon-carbon / graphite negative electrode materials through the design of the composite material structure.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is: A composite material based on a graphite particle core and a porous carbon shell, wherein the porous carbon accounts for 2% to 50% of the composite material by mass; the specific surface area of the composite material is 20 to 1458 m 2 / g, with a total pore volume of 0.01-0.74cm 3 / g, the proportion of micropore volume to total pore volume is 80%-96%, and the average pore diameter is 1.62-2.33nm.
[0007] The present invention also provides a method for preparing the above-mentioned composite material based on a graphite particle core and a porous carbon shell, which comprises mixing graphite particles and a coating agent, carbonizing to obtain a graphite particle core-carbon shell structure, adding an activator to activate and form pores, and obtaining the composite material.
[0008] As a limitation, the coating agent includes phenolic resin or asphalt, and the activating agent includes water vapor, carbon dioxide or potassium hydroxide.
[0009] As a further limitation, the coating agent accounts for 5%-80% of the total mass of the graphite particles and the coating agent, and the mass ratio of the carbon shell to the activator is 1:1-10.
[0010] As another limitation, the carbonization is carried out at a temperature of 600° C. for a time of 2 h in a nitrogen atmosphere.
[0011] As a third limitation, the activation temperature is 800-900° C. and the time is 2-5 h.
[0012] The present invention also provides an application of the above-mentioned composite material based on a graphite particle core and a porous carbon shell, and the composite material is used as a carrier to prepare a CVD silicon-carbon / graphite negative electrode material.
[0013] Due to the adoption of the above technical solution, the present invention has the following technical advances compared with the prior art: The present invention provides a composite material based on a graphite particle core and a porous carbon shell, a preparation method and an application thereof. The graphite particles are first mixed with a coating agent and carbonized to obtain a graphite particle core-carbon shell structure, and then an activator is used to activate and form pores. Since it is difficult for activators such as water vapor, carbon dioxide and potassium hydroxide to form pores in graphite particles, all the pores are distributed in the carbon shell, thereby forming a composite material of the graphite particle core and the porous carbon shell. Silicon is then vapor deposited and carbon is coated to obtain a negative electrode material. A CVD silicon-carbon material with poor electrical conductivity, slow lithium ion diffusion rate and large volume expansion is coated on the surface of the graphite particles. The silicon-carbon material with slower kinetics contacts lithium ions and electrons before the graphite particles, so that the rate performance of each particle is closer. Compared with the conventional method of directly mixing the CVD silicon-carbon material with graphite, the rate performance and cycle stability of the negative electrode material are significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 Schematic diagram of the preparation process of the composite material based on the graphite particle core and the porous carbon shell in Example 1; Figure 2 Schematic diagram of the preparation process of CVD silicon carbon / graphite negative electrode material in Example 19. DETAILED DESCRIPTION
[0015] The present invention is further described in detail below by specific examples. It should be understood that the described examples are only used to explain the present invention, and are not intended to limit the present invention.
[0016] Unless otherwise specified, the experimental methods used in the following examples are conventional methods in the art.
[0017] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0018] Example 1 In this embodiment, a composite material based on a graphite particle core and a porous carbon shell is prepared. The schematic diagram of the preparation process is shown in FIG. Figure 1As shown, the specific steps include: Phenolic resin and asphalt (coating agent) were subjected to thermogravimetric analysis in a nitrogen atmosphere, respectively, with a heating rate of 1°C / min, to obtain the carbonization mass yield of phenolic resin or asphalt at different temperatures. Since the weight loss rate of the phenolic resin and asphalt used slowed down significantly after the temperature reached 600°C, the carbonization temperature of the phenolic resin and asphalt was set at 600°C, and the holding time was 2h. Under this condition, the carbonization mass yields of phenolic resin and asphalt were 62% and 65%, respectively. The graphite particles and the phenolic resin coating agent are mixed evenly (the mass of the phenolic resin coating agent accounts for 5.46% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, water vapor is added (the mass ratio of the carbon shell to water vapor is 1:3), and the mixture is kept warm at 850°C for 3 hours to activate and form pores, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0019] The mass percentage of porous carbon in the composite material is 2%. The specific surface area of the composite material is 23.2 m 2 / g, and the total pore volume is 0.0102cm 3 / g, the proportion of micropore volume to total pore volume is 92%, and the average pore diameter is 1.76nm.
[0020] Example 2 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the phenolic resin coating agent are mixed evenly (the mass of the phenolic resin coating agent accounts for 6.68% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure. Water vapor is added (the mass ratio of the carbon shell to water vapor is 1:4), and the mixture is kept warm at 850°C for 3 hours to activate and form pores. The mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0021] The calculation shows that the porous carbon accounts for 2% of the composite material by mass. The test shows that the specific surface area of the composite material is 30.8 m 2 / g, and the total pore volume is 0.0152cm 3 / g, the proportion of micropore volume to total pore volume is 85%, and the average pore diameter is 1.98nm.
[0022] Example 3 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the phenolic resin coating agent are mixed evenly (the mass of the phenolic resin coating agent accounts for 9.60% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, water vapor is added (the mass ratio of the carbon shell to water vapor is 1:5), and the mixture is kept warm at 850°C for 3 hours to activate and form pores, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0023] The calculation shows that the porous carbon accounts for 2% of the composite material by mass. The test shows that the specific surface area of the composite material is 38.7 m 2 / g, and the total pore volume is 0.0212cm 3 / g, the proportion of micropore volume to total pore volume is 81%, and the average pore diameter is 2.20nm.
[0024] Example 4 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the asphalt coating agent are evenly mixed (the mass of the asphalt coating agent accounts for 5.05% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure. Water vapor is added (the mass ratio of the carbon shell to water vapor is 1:4), and the mixture is kept warm at 850°C for 3 hours to activate and form pores. The mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0025] The calculation shows that the porous carbon accounts for 2% of the composite material by mass. The test shows that the specific surface area of the composite material is 20.5 m 2 / g, and the total pore volume is 0.0102cm 3 / g, the proportion of micropore volume to total pore volume is 87%, and the average pore diameter is 1.96nm.
[0026] Example 5 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the asphalt coating agent are evenly mixed (the mass of the asphalt coating agent accounts for 15.25% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure. Water vapor is added (the mass ratio of the carbon shell to water vapor is 1:6), and the mixture is kept warm at 850°C for 3 hours to activate and form pores. The mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0027] The calculation shows that the porous carbon accounts for 5% of the composite material by mass. The test shows that the specific surface area of the composite material is 75.8m 2 / g, and the total pore volume is 0.04cm 3 / g, the proportion of micropore volume to total pore volume is 83%, and the average pore diameter is 2.07nm.
[0028] Example 6 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the asphalt coating agent are evenly mixed (the mass of the asphalt coating agent accounts for 36.30% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure. Water vapor is added (the mass ratio of the carbon shell to water vapor is 1:8), and the mixture is kept warm at 850°C for 3 hours to activate and form pores. The mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0029] According to calculation, the mass percentage of porous carbon in the composite material is 10%. According to testing, the specific surface area of the composite material is 206.8m 2 / g, and the total pore volume is 0.113cm 3 / g, the proportion of micropore volume to total pore volume is 80%, and the average pore diameter is 2.20nm.
[0030] Example 7 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the phenolic resin coating agent are mixed evenly (the mass of the phenolic resin coating agent accounts for 31.12% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, carbon dioxide is added (the mass ratio of the carbon shell to carbon dioxide is 1:4), and the mixture is kept warm at 900°C for 5 hours to activate and form pores, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0031] According to calculation, the mass percentage of porous carbon in the composite material is 15%. According to testing, the specific surface area of the composite material is 162.3m 2 / g, and the total pore volume is 0.0825cm 3 / g, the proportion of micropore volume to total pore volume is 86%, and the average pore diameter is 1.99nm.
[0032] Example 8 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the phenolic resin coating agent are mixed evenly (the mass of the phenolic resin coating agent accounts for 48.39% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, carbon dioxide is added (the mass ratio of the carbon shell to carbon dioxide is 1:6), and the mixture is kept warm at 900°C for 5 hours to activate and form pores, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0033] According to calculation, the mass percentage of porous carbon in the composite material is 20%. According to testing, the specific surface area of the composite material is 291m 2 / g, with a total pore volume of 0.15 cm 3 / g, the proportion of micropore volume to total pore volume is 82%, and the average pore diameter is 2.11nm.
[0034] Example 9 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the phenolic resin coating agent are mixed evenly (the mass of the phenolic resin coating agent accounts for 60.57% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, carbon dioxide is added (the mass ratio of the carbon shell to carbon dioxide is 1:7), and the mixture is kept warm at 900°C for 5 hours to activate and form pores, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0035] According to calculation, the mass percentage of porous carbon in the composite material is 25%. According to testing, the specific surface area of the composite material is 406m 2 / g, and the total pore volume is 0.2275cm 3 / g, the proportion of micropore volume to total pore volume is 80%, and the average pore diameter is 2.33nm.
[0036] Example 10 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the asphalt coating agent are evenly mixed (the mass of the asphalt coating agent accounts for 50.74% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure. Carbon dioxide (the mass ratio of the carbon shell to carbon dioxide is 1:6) is added, and the mixture is kept warm at 900°C for 5 hours to activate and form pores. The mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0037] According to calculation, the mass percentage of porous carbon in the composite material is 30%. According to testing, the specific surface area of the composite material is 302.1m 2 / g, and the total pore volume is 0.156cm 3 / g, the proportion of micropore volume to total pore volume is 85%, and the average pore diameter is 2.02nm.
[0038] Embodiment 11 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the asphalt coating agent are evenly mixed (the mass of the asphalt coating agent accounts for 64.30% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, carbon dioxide is added (the mass ratio of the carbon shell to carbon dioxide is 1:8), and the mixture is kept warm at 900°C for 5 hours to activate and form pores, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0039] The calculation shows that the porous carbon accounts for 35% of the composite material by mass. The test shows that the specific surface area of the composite material is 528.8 m 2 / g, and the total pore volume is 0.273cm 3 / g, the proportion of micropore volume to total pore volume is 83%, and the average pore diameter is 2.09nm.
[0040] Example 12 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the asphalt coating agent are evenly mixed (the mass of the asphalt coating agent accounts for 75.66% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, carbon dioxide is added (the mass ratio of the carbon shell to carbon dioxide is 1:10), and the mixture is kept warm at 900°C for 5 hours to activate and form pores, and the mixture is cooled to room temperature under a nitrogen atmosphere to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0041] According to calculation, the mass percentage of porous carbon in the composite material is 40%. According to testing, the specific surface area of the composite material is 692.8m 2 / g, with a total pore volume of 0.38 cm 3 / g, the proportion of micropore volume to total pore volume is 81%, and the average pore diameter is 2.26nm.
[0042] Embodiment 13 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the phenolic resin coating agent are mixed evenly (the mass of the phenolic resin coating agent accounts for 66.66% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, potassium hydroxide is added (the mass ratio of the carbon shell to potassium hydroxide is 1:1), and the mixture is kept warm at 800°C for 2 hours to activate and form pores, and the mixture is cooled to room temperature under a nitrogen atmosphere, and washed gradually with hydrochloric acid and water, and then dried to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0043] The calculation shows that the porous carbon accounts for 45% of the composite material by mass. The specific surface area of the composite material is 615.6 m 2 / g, and the total pore volume is 0.243cm 3 / g, the proportion of micropore volume to total pore volume is 96%, and the average pore diameter is 1.62nm.
[0044] Embodiment 14 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the phenolic resin coating agent are mixed evenly (the mass of the phenolic resin coating agent accounts for 75.27% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, potassium hydroxide is added (the mass ratio of the carbon shell to potassium hydroxide is 1:2), and the mixture is kept warm at 800°C for 2 hours to activate and form pores, and the mixture is cooled to room temperature under a nitrogen atmosphere, and gradually washed with hydrochloric acid and water, and then dried to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0045] According to calculation, the mass percentage of porous carbon in the composite material is 50%. According to testing, the specific surface area of the composite material is 1069.5m 2 / g, and the total pore volume is 0.485cm 3 / g, the proportion of micropore volume to total pore volume is 90%, and the average pore diameter is 1.88nm.
[0046] Embodiment 15 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the phenolic resin coating agent are mixed evenly (the mass of the phenolic resin coating agent accounts for 79.73% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, potassium hydroxide is added (the mass ratio of the carbon shell to potassium hydroxide is 1:4), and the mixture is kept warm at 800°C for 2 hours to activate and form pores, and the mixture is cooled to room temperature under a nitrogen atmosphere, and washed gradually with hydrochloric acid and water, and then dried to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0047] According to calculation, the mass percentage of porous carbon in the composite material is 50%. According to testing, the specific surface area of the composite material is 1457.5m 2 / g, and the total pore volume is 0.735cm 3 / g, the proportion of micropore volume to total pore volume is 85%, and the average pore diameter is 2.04nm.
[0048] Example 16 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the asphalt coating agent are mixed evenly (the mass of the asphalt coating agent accounts for 70.62% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, potassium hydroxide is added (the mass ratio of the carbon shell to potassium hydroxide is 1:1), and the mixture is kept warm at 800°C for 2 hours to activate and form pores. The mixture is cooled to room temperature under a nitrogen atmosphere, and washed gradually with hydrochloric acid and water, and then dried to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0049] According to calculation, the mass percentage of porous carbon in the composite material is 50%. According to testing, the specific surface area of the composite material is 625m 2 / g, with a total pore volume of 0.275 cm 3 / g, the proportion of micropore volume to total pore volume is 95%, and the average pore diameter is 1.68nm.
[0050] Embodiment 17 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the asphalt coating agent are mixed evenly (the mass of the asphalt coating agent accounts for 49.65% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, potassium hydroxide is added (the mass ratio of the carbon shell to potassium hydroxide is 1:2), and the mixture is kept warm at 800°C for 2 hours to activate and form pores. The mixture is cooled to room temperature under a nitrogen atmosphere, and washed gradually with hydrochloric acid and water, and then dried to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0051] According to calculation, the mass percentage of porous carbon in the composite material is 25%. According to testing, the specific surface area of the composite material is 501.8m 2 / g, and the total pore volume is 0.2325cm 3 / g, the proportion of micropore volume to total pore volume is 90%, and the average pore diameter is 1.91nm.
[0052] Embodiment 18 This embodiment prepares a composite material based on a graphite particle core and a porous carbon shell, which specifically includes the following steps: The graphite particles and the asphalt coating agent are evenly mixed (the mass of the asphalt coating agent accounts for 6.66% of the total mass of the two), the mixture is placed in a carbonization furnace, and the temperature is increased to 600°C at a rate of 2°C / min under a nitrogen atmosphere, and then kept warm for 2 hours to obtain a graphite particle core-carbon shell structure, potassium hydroxide is added (the mass ratio of the carbon shell to potassium hydroxide is 1:4), and the mixture is kept warm at 800°C for 2 hours to activate and form pores. The mixture is cooled to room temperature under a nitrogen atmosphere, and washed gradually with hydrochloric acid and water, and then dried to obtain a composite material based on a graphite particle core and a porous carbon shell.
[0053] The calculated mass percentage of porous carbon in the composite material is 2%. The specific surface area of the composite material is 56.44 m 2 / g, and the total pore volume is 0.029cm 3 / g, the proportion of micropore volume to total pore volume is 84%, and the average pore diameter is 2.09nm.
[0054] Embodiment 19 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The schematic diagram of the preparation process is shown in FIG. Figure 2 As shown, the specific preparation comprises the following steps: Weigh 1.5 kg of the composite material prepared in Example 1 (wherein the mass of the porous carbon is 0.03 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500 ° C at a rate of 5 ° C / min (the utilization rate of monosilane at this temperature is 85%), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, the mass ratio of deposited silicon to porous carbon is controlled to be 2: 3 (this mass ratio is set based on the pore volume of the porous carbon), after the introduction time is 9.3 min, stop introducing monosilane, after the temperature is increased to 600 ° C at a rate of 5 ° C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0055] Embodiment 20 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 2 (wherein the mass of the porous carbon is 0.03 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500 ° C at a rate of 5 ° C / min (the utilization rate of monosilane at this temperature is 85%), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, the mass ratio of deposited silicon to porous carbon is controlled to be 1: 1 (this mass ratio is set based on the pore volume of the porous carbon), after the introduction time is 14.0 min, stop introducing monosilane, after the temperature is increased to 600 ° C at a rate of 5 ° C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0056] Embodiment 21 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 3 (wherein the mass of the porous carbon is 0.03 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500 ° C at a rate of 5 ° C / min (the utilization rate of monosilane at this temperature is 85%), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, the mass ratio of deposited silicon to porous carbon is controlled to be 3: 2 (this mass ratio is set based on the pore volume of the porous carbon), after the introduction time is 21.0 min, stop introducing monosilane, after the temperature is increased to 600 ° C at a rate of 5 ° C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0057] Embodiment 22 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 4 (wherein the mass of the porous carbon is 0.03 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500 ° C at a rate of 5 ° C / min (the utilization rate of monosilane at this temperature is 85%), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 1.5 L / min, control the mass ratio of deposited silicon to porous carbon to be 2: 3 (this mass ratio is set based on the pore volume of the porous carbon), stop introducing monosilane after the introduction time is 12.5 min, and start introducing acetylene after the temperature is increased to 600 ° C at a rate of 5 ° C / min, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0058] Embodiment 23 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 5 (wherein the mass of the porous carbon is 0.075 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500 ° C at a rate of 5 ° C / min (the utilization rate of monosilane at this temperature is 85%), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2.5 L / min, control the mass ratio of deposited silicon to porous carbon to be 1: 1 (this mass ratio is set based on the pore volume of the porous carbon), stop introducing monosilane after the introduction time is 28.0 min, and start introducing acetylene after the temperature is increased to 600 ° C at a rate of 5 ° C / min, the acetylene flow rate is 2 L / min, the introduction time is 1h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0059] Embodiment 24 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 6 (wherein the mass of the porous carbon is 0.15 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500 ° C at a rate of 5 ° C / min (the utilization rate of monosilane at this temperature is 85%), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, the mass ratio of deposited silicon to porous carbon is controlled to be 3: 2 (this mass ratio is set based on the pore volume of the porous carbon), after the introduction time is 105.1 min, stop introducing monosilane, after the temperature is increased to 600 ° C at a rate of 5 ° C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0060] Embodiment 25 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 7 (wherein the mass of the porous carbon is 0.225 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500 ° C at a rate of 5 ° C / min (the utilization rate of monosilane at this temperature is 85%), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, the mass ratio of deposited silicon to porous carbon is controlled to be 2: 3 (this mass ratio is set based on the pore volume of the porous carbon), after the introduction time is 70.1 min, stop introducing monosilane, after the temperature is increased to 600 ° C at a rate of 5 ° C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0061] Embodiment 26 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 8 (wherein the mass of the porous carbon is 0.3 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 475 ° C at a rate of 5 ° C / min (the utilization rate of monosilane at this temperature is 81%), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, control the mass ratio of deposited silicon to porous carbon to be 1: 1 (this mass ratio is set based on the pore volume of the porous carbon), stop introducing monosilane after the introduction time is 147.1 min, and start introducing acetylene after the temperature is increased to 600 ° C at a rate of 5 ° C / min, the acetylene flow rate is 2 L / min, the introduction time is 1h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0062] Embodiment 27 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 9 (wherein the mass of the porous carbon is 0.375 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 525 ° C at a rate of 5 ° C / min (the utilization rate of monosilane at this temperature is 88%), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, control the mass ratio of deposited silicon to porous carbon to be 3: 2 (this mass ratio is set based on the pore volume of the porous carbon), stop introducing monosilane after the introduction time is 253.8 min, and start introducing acetylene after the temperature is increased to 600 ° C at a rate of 5 ° C / min, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0063] Embodiment 28 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 10 (wherein the mass of the porous carbon is 0.45 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500 ° C at a rate of 5 ° C / min (the utilization rate of monosilane at this temperature is 85%), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, the mass ratio of deposited silicon to porous carbon is controlled to be 2: 3 (this mass ratio is set based on the pore volume of the porous carbon), after the introduction time is 140.1 min, stop introducing monosilane, after the temperature is increased to 600 ° C at a rate of 5 ° C / min, start introducing acetylene, the acetylene flow rate is 1.5 L / min, the introduction time is 1.33 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0064] Embodiment 29 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 11 (wherein the mass of the porous carbon is 0.525 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500° C. at a rate of 5° C. / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 1:1 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 245.3 min, stop introducing monosilane, and after the temperature is increased to 600° C. at a rate of 5° C. / min, start introducing acetylene, the acetylene flow rate is 2.5 L / min, the introduction time is 0.8 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon-carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0065] Embodiment 30 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 12 (wherein the mass of the porous carbon is 0.6 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500° C. at a rate of 5° C. / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 3:2 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 420.4 min, stop introducing monosilane, and after the temperature is increased to 600° C. at a rate of 5° C. / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon-carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 1.5 L / min for 2.67 h. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0066] Embodiment 31 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 13 (wherein the mass of the porous carbon is 0.675 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 2:3 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 210.2 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon-carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After heating to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2.5 L / min for 1.6 h. The introduction of acetylene was stopped and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0067] Embodiment 32 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 14 (wherein the mass of the porous carbon is 0.75 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500° C. at a rate of 5° C. / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 1:1 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 350.4 min, stop introducing monosilane, and after the temperature is increased to 575° C. at a rate of 5° C. / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon-carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 575°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0068] Embodiment 33 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 15 (wherein the mass of the porous carbon is 0.75 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500° C. at a rate of 5° C. / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 3:2 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 525.5 min, stop introducing monosilane, and after the temperature is increased to 625° C. at a rate of 5° C. / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon-carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 625°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0069] Embodiment 34 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 16 (wherein the mass of the porous carbon is 0.75 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 2:3 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 233.6 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon-carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0070] Embodiment 35 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 17 (wherein the mass of the porous carbon is 0.375 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, control the mass ratio of deposited silicon to porous carbon to be 1:1 (this mass ratio is set based on the pore volume of the porous carbon), stop introducing monosilane after the introduction time is 175.2 min, and start introducing acetylene after the temperature is increased to 600°C at a rate of 5°C / min, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a primary carbon-coated CVD silicon-carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0071] Embodiment 36 This embodiment provides an application of a composite material based on a graphite particle core and a porous carbon shell, which is used as a carrier to prepare a CVD silicon carbon / graphite negative electrode material. The specific preparation includes the following steps: Weigh 1.5 kg of the composite material prepared in Example 18 (wherein the mass of the porous carbon is 0.03 kg), transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 3:2 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 21.0 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, and the introduction time is 1 h. Stop introducing acetylene and cool naturally to room temperature to obtain a primary carbon-coated CVD silicon-carbon / graphite negative electrode material; The primary carbon-coated CVD silicon-carbon / graphite negative electrode material was transferred to the secondary carbon-coating equipment, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature). After the temperature was raised to 600°C at a rate of 5°C / min, acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon / graphite negative electrode material.
[0072] Comparative Example 1 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The phenolic resin was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the phenolic resin carbonized material was obtained. Water vapor was added for activation. The activation conditions were 850°C and the holding time was 3 hours. The mass ratio of the phenolic resin carbonized material to water vapor was 1:3. The specific surface area of the prepared porous carbon was 1159 m 2 / g, pore volume is 0.51cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon equipment, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 2:3 (this mass ratio is set based on the pore volume of porous carbon). After the introduction time is 467.1 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 2.38%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 19.
[0073] Comparative Example 2 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The phenolic resin was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the phenolic resin carbonized material was obtained. Water vapor was added for activation. The activation conditions were 850°C and the holding time was 3 hours. The mass ratio of the phenolic resin carbonized material to water vapor was 1:4. The specific surface area of the prepared porous carbon was 1539m 2 / g, pore volume is 0.76cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 1:1 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 700.7 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 3.46%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 20.
[0074] Comparative Example 3 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The phenolic resin was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the phenolic resin carbonized material was obtained. Water vapor was added for activation. The activation conditions were 850°C and the holding time was 3 hours. The mass ratio of the phenolic resin carbonized material to water vapor was 1:5. The specific surface area of the prepared porous carbon was 1937m 2 / g, pore volume is 1.06cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 3:2 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 1051.1 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 1.69%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 21.
[0075] Comparative Example 4 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The asphalt was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the asphalt carbonized material was obtained. Water vapor was added for activation. The activation conditions were 850°C and the insulation time was 3 hours. The mass ratio of asphalt carbonized material to water vapor was 1:4. The specific surface area of the prepared porous carbon was 1026m 2 / g, pore volume is 0.51cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon equipment, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 1.5 L / min, control the mass ratio of deposited silicon to porous carbon to be 2:3 (this mass ratio is set based on the pore volume of porous carbon), stop introducing monosilane after the introduction time is 622.9 min, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 2.38%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 22.
[0076] Comparative Example 5 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The asphalt was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the asphalt carbonized material was obtained. Water vapor was added for activation. The activation conditions were 850°C and the insulation time was 3 hours. The mass ratio of asphalt carbonized material to water vapor was 1:6. The specific surface area of the prepared porous carbon was 1517m 2 / g, pore volume is 0.80cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon equipment, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2.5 L / min, control the mass ratio of deposited silicon to porous carbon to be 1:1 (this mass ratio is set based on the pore volume of porous carbon), stop introducing monosilane after the introduction time is 560.6 min, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 9.00%. The negative electrode material prepared at this time has a specific capacity similar to that of Example 23.
[0077] Comparative Example 6 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The asphalt was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the asphalt carbonized material was obtained. Water vapor was added for activation. The activation conditions were 850°C and the insulation time was 3 hours. The mass ratio of asphalt carbonized material to water vapor was 1:8. The specific surface area of the prepared porous carbon was 2068m 2 / g, pore volume is 1.13cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 3:2 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 1051.1 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 22.11%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 24.
[0078] Comparative Example 7 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The phenolic resin was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the phenolic resin carbonized material was obtained. Carbon dioxide was added for activation. The activation conditions were 900°C and the holding time was 5 hours. The mass ratio of the phenolic resin carbonized material to carbon dioxide was 1:4. The specific surface area of the prepared porous carbon was 1082 m 2 / g, pore volume is 0.55cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon equipment, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 2:3 (this mass ratio is set based on the pore volume of porous carbon). After the introduction time is 467.1 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 19.26%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 25.
[0079] Comparative Example 8 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The phenolic resin was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the phenolic resin carbonized material was obtained. Carbon dioxide was added for activation. The activation conditions were 900°C and the holding time was 5 hours. The mass ratio of the phenolic resin carbonized material to carbon dioxide was 1:6. The specific surface area of the prepared porous carbon was 1455m 2 / g, pore volume is 0.75cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 475°C at a rate of 5°C / min (the utilization rate of monosilane is 81% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, control the mass ratio of deposited silicon to porous carbon to be 1:1 (this mass ratio is set based on the pore volume of porous carbon), stop introducing monosilane after the introduction time is 735.5 min, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 32.81%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 26.
[0080] Comparative Example 9 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The phenolic resin was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the phenolic resin carbonized material was obtained. Carbon dioxide was added for activation. The activation conditions were 900°C and the holding time was 5 hours. The mass ratio of the phenolic resin carbonized material to carbon dioxide was 1:7. The specific surface area of the prepared porous carbon was 1624m 2 / g, pore volume is 0.91cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 525°C at a rate of 5°C / min (the utilization rate of monosilane is 88% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 3:2 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 1015.3 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 47.05%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 27.
[0081] Comparative Example 10 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The asphalt was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the asphalt carbonized material was obtained. Carbon dioxide was added for activation. The activation conditions were 900°C and the holding time was 5 hours. The mass ratio of asphalt carbonized material to carbon dioxide was 1:6. The specific surface area of the prepared porous carbon was 1007m 2 / g, pore volume is 0.52cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 2:3 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 467.1 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 1.5 L / min, the introduction time is 1.33 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 35.87%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 28.
[0082] Comparative Example 11 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The asphalt was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the asphalt carbonized material was obtained. Carbon dioxide was added for activation. The activation conditions were 900°C and the holding time was 5 hours. The mass ratio of asphalt carbonized material to carbon dioxide was 1:8. The specific surface area of the prepared porous carbon was 1511m 2 / g, pore volume is 0.78cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon equipment, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, control the mass ratio of deposited silicon to porous carbon to be 1:1 (this mass ratio is set based on the pore volume of porous carbon), stop introducing monosilane after the introduction time is 700.7 min, and start introducing acetylene after the temperature is increased to 600°C at a rate of 5°C / min, the acetylene flow rate is 2.5 L / min, the introduction time is 0.8 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 51.57%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 29.
[0083] Comparative Example 12 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The asphalt was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the asphalt carbonized material was obtained. Carbon dioxide was added for activation. The activation conditions were 900°C and the holding time was 5 hours. The mass ratio of asphalt carbonized material to carbon dioxide was 1:10. The specific surface area of the prepared porous carbon was 1732m 2 / g, pore volume is 0.95cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 3:2 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 1051.1 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 1.5 L / min for 2.67 h. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 65.26%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 30.
[0084] Comparative Example 13 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The phenolic resin was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the phenolic resin carbonized material was obtained. Potassium hydroxide was added for activation. The activation conditions were 800°C and the holding time was 2 hours. The mass ratio of the phenolic resin carbonized material to potassium hydroxide was 1:1. After that, it was washed with hydrochloric acid, washed with water, and dried in sequence. The specific surface area of the prepared porous carbon was 1368m 2 / g, pore volume is 0.54cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon equipment, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 2:3 (this mass ratio is set based on the pore volume of porous carbon). After the introduction time is 467.1 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2.5 L / min for 1.6 h. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 50.05%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 31.
[0085] Comparative Example 14 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The phenolic resin was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the phenolic resin carbonized material was obtained. Potassium hydroxide was added for activation. The activation conditions were 800°C and the holding time was 2 hours. The mass ratio of the phenolic resin carbonized material to potassium hydroxide was 1:2. After that, it was washed with hydrochloric acid, washed with water, and dried in sequence. The specific surface area of the prepared porous carbon was 2139 m 2 / g, pore volume is 0.97cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, control the mass ratio of deposited silicon to porous carbon to be 1:1 (this mass ratio is set based on the pore volume of the porous carbon), stop introducing monosilane after the introduction time is 700.7 min, and start introducing acetylene after the temperature is increased to 575°C at a rate of 5°C / min, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained constant until it dropped to room temperature), and the temperature was raised to 575°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 66.74%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 32.
[0086] Comparative Example 15 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The phenolic resin was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the phenolic resin carbonized material was obtained. Potassium hydroxide was added for activation. The activation conditions were 800°C and the holding time was 2 hours. The mass ratio of the phenolic resin carbonized material to potassium hydroxide was 1:4. After that, it was washed with hydrochloric acid, washed with water, and dried in sequence. The specific surface area of the prepared porous carbon was 2915m 2 / g, pore volume is 1.47cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 3:2 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 1051.1 min, stop introducing monosilane, and after the temperature is increased to 625°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained constant until it dropped to room temperature), and the temperature was raised to 625°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 74.89%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 33.
[0087] Comparative Example 16 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The asphalt was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the asphalt carbonized material was obtained. Potassium hydroxide was added for activation. The activation conditions were 800°C and the holding time was 2 hours. The mass ratio of the asphalt carbonized material to potassium hydroxide was 1:1. After that, it was washed with hydrochloric acid, washed with water, and dried in sequence. The specific surface area of the prepared porous carbon was 1250m 2 / g, pore volume is 0.55cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon equipment, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 2:3 (this mass ratio is set based on the pore volume of porous carbon). After the introduction time is 467.1 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 54.32%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 34.
[0088] Comparative Example 17 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The asphalt was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the asphalt carbonized material was obtained. Potassium hydroxide was added for activation. The activation conditions were 800°C and the holding time was 2 hours. The mass ratio of the asphalt carbonized material to potassium hydroxide was 1:2. After that, it was washed with hydrochloric acid, washed with water, and dried in sequence. The specific surface area of the prepared porous carbon was 2007m 2 / g, pore volume is 0.93cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 1:1 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 700.7 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 39.54%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 35.
[0089] Comparative Example 18 This comparative example provides a traditional method for preparing CVD silicon carbon / graphite negative electrode material, which specifically includes the following steps: S1. Preparation of porous carbon The asphalt was placed in a carbonization furnace and heated to 600°C at a rate of 2°C / min under a nitrogen atmosphere. After being kept warm for 2 hours, the asphalt carbonized material was obtained. Potassium hydroxide was added for activation. The activation conditions were 800°C and the holding time was 2 hours. The mass ratio of the asphalt carbonized material to potassium hydroxide was 1:4. After that, it was washed with hydrochloric acid, washed with water, and dried in sequence. The specific surface area of the prepared porous carbon was 2822 m 2 / g, pore volume is 1.45cm 3 / g; S2. Preparation of CVD silicon-carbon materials Weigh 1.5 kg of porous carbon, transfer it to a vapor deposition silicon device, introduce nitrogen, the nitrogen flow rate is 15 L / min (the nitrogen flow rate remains unchanged until it drops to room temperature), heat up to 500°C at a rate of 5°C / min (the utilization rate of monosilane is 85% at this temperature), introduce monosilane (density calculated according to 1.44 g / L), the monosilane flow rate is 2 L / min, and the mass ratio of deposited silicon to porous carbon is controlled to be 3:2 (this mass ratio is set based on the pore volume of the porous carbon). After the introduction time is 1051.1 min, stop introducing monosilane, and after the temperature is increased to 600°C at a rate of 5°C / min, start introducing acetylene, the acetylene flow rate is 2 L / min, the introduction time is 1 h, stop introducing acetylene, and naturally cool to room temperature to obtain a once carbon-coated CVD silicon-carbon material; The primary carbon-coated CVD silicon-carbon material was transferred to a secondary carbon-coating device, and nitrogen was introduced at a nitrogen flow rate of 10 L / min (the nitrogen flow rate remained unchanged until it dropped to room temperature), and the temperature was raised to 600°C at a rate of 5°C / min, and acetylene was introduced at an acetylene flow rate of 2 L / min for 2 hours. The introduction of acetylene was stopped, and the temperature was naturally lowered to room temperature to obtain a secondary carbon-coated CVD silicon-carbon material; S3. Mixing graphite to prepare negative electrode materials Take the secondary carbon-coated CVD silicon-carbon material and add graphite to mix evenly to obtain the CVD silicon-carbon / graphite negative electrode material, wherein the mass percentage of the secondary carbon-coated CVD silicon-carbon material in the negative electrode material is 4.63%. The specific capacity of the negative electrode material prepared at this time is similar to that of Example 36.
[0090] Performance Testing The negative electrode materials prepared in Examples 19-36 and Comparative Examples 1-18 were assembled into batteries, and their related performances were tested, specifically including the following steps: S1. Preparation of negative electrode sheet 4.75 g of N-methylpyrrolidone, 0.25 g of polyvinylidene fluoride, 0.25 g of conductive carbon black Super P and 4.5 g of the negative electrode materials prepared in Examples 19-36 and Comparative Examples 1-18 were placed in a plastic container for slurrying to obtain a black viscous slurry, which was evenly coated on the surface of a copper foil with a scraper to form slurry films with a thickness of 200 μm and 100 μm, respectively (wherein the 100 μm slurry film was only used for rate performance testing), dried at 120° C., rolled, cut into circular pole pieces with a diameter of 11 mm, and weighed to calculate the actual negative electrode material loading on each pole piece; S2. Assemble lithium-ion batteries A metal lithium sheet with a diameter of 15.6 mm and a thickness of 450 μm was used as the counter electrode, a Celgard 2325 with a diameter of 16.5 mm and a thickness of 20 μm was used as the separator, and the prepared 11 mm negative electrode sheet was used as the working electrode. LiPF6 (1 mol / L) was dissolved in a mixed solution of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate (volume ratio 1:1:1), and then 5 wt% fluoroethylene carbonate solution was added as the electrolyte to assemble a 2032 type button battery. Six batteries were assembled for each negative electrode material, and a total of six groups of data were tested. After removing the highest and lowest data, the average value of the remaining four groups of data was taken as the battery performance data; S3. Performance test At room temperature of 25°C, the assembled lithium-ion battery was discharged to 0.005V at 0.1C using a blue electric tester, left to stand for 2 minutes, and then discharged to 0.005V at 0.05C. After standing for another 2 minutes, the discharge procedure was terminated by discharging to 0.005V at 0.02C. After standing for 2 minutes, the battery was charged to 1.5V at 0.1C. The ratio of the charge specific capacity to the discharge specific capacity is the first coulombic efficiency at 1.5V. The battery is discharged to 0.005V at 0.2C, and then allowed to stand for 2 minutes. Then, it is discharged to 0.005V at 0.05C, and then allowed to stand for 2 minutes. Then, it is charged to 1.5V at 0.2C. The ratio of the charging capacity after 25 cycles to the first charging capacity (the first time charged at 0.2C) is the capacity retention rate. The first cycle full charge expansion rate is obtained by testing the ratio of the electrode thickness after the first cycle of charging (without the copper foil) to the electrode thickness before the cycle (without the copper foil). The rate test conditions are to discharge the battery to 0.005V at 0.2C, 1C, 2C, and 3C, respectively, and then continue to discharge to 0.005V at 0.05C after standing for 2 minutes. After standing for 2 minutes, the battery is charged to 1.5V at 0.2C, 1C, 2C, and 3C respectively. The ratio of the charge capacity obtained at 1C, 2C, and 3C to the charge capacity at 0.2C is the capacity retention rate at different rates. The specific test results are shown in Table 1: Table 1 Battery performance test results As can be seen from Table 1, by comparing Examples 19-36 and Comparative Examples 1-18, respectively, under the condition of similar battery specific capacity, the negative electrode material with a special structure prepared by the method of the present invention (graphite particles as the core, porous carbon as the shell CVD deposited silicon carbon) is superior to the traditional negative electrode material prepared by directly mixing porous carbon-based CVD silicon carbon and graphite in the first coulombic efficiency, capacity retention rate, first week full charge expansion rate, and capacity retention rate at different rates of the lithium ion battery. This proves that the negative electrode material prepared by the method of the present invention can significantly improve the cycle life and rate performance of lithium ion batteries, which is of great significance to the development of lithium ion batteries.
Claims
1. A composite material based on a graphite particle core and a porous carbon shell, characterized in that: The porous carbon accounts for 2% to 50% of the composite material by mass; the specific surface area of the composite material is 20 to 1458 m 2 / g, with a total pore volume of 0.01-0.74cm 3 / g, the proportion of micropore volume to total pore volume is 80%-96%, and the average pore diameter is 1.62-2.33nm.
2. The method for preparing a composite material based on a graphite particle core and a porous carbon shell according to claim 1, characterized in that: The method comprises mixing graphite particles and a coating agent, carbonizing the mixture to obtain a graphite particle core-carbon shell structure, adding an activator to activate the mixture and form pores, thereby obtaining a composite material.
3. The preparation method according to claim 2, characterized in that: The coating agent includes phenolic resin or asphalt, and the activating agent includes water vapor, carbon dioxide or potassium hydroxide.
4. The preparation method according to claim 3, characterized in that: The coating agent accounts for 5%-80% of the total mass of the graphite particles and the coating agent, and the mass ratio of the carbon shell to the activator is 1:1-10.
5. The preparation method according to any one of claims 2 to 4, characterized in that: The carbonization temperature is 600° C., the time is 2 h, and the process is carried out in a nitrogen atmosphere.
6. The preparation method according to any one of claims 2 to 4, characterized in that: The activation temperature is 800-900° C. and the time is 2-5 hours.
7. The use of a composite material based on a graphite particle core and a porous carbon shell according to claim 1, characterized in that: The composite material is used as a carrier to prepare CVD silicon-carbon / graphite negative electrode material.